(untitled) (Transactions of the Association of European Schools of Planning, 2019)
The paper proposes a reflection on the Mapping San Siro experience, a five-year action learning project, promoted by the Department of Architecture and Urban Studies in collaboration with Polisocial, the public engagement program of Politecnico di Milano. The project is currently ongoing in one of the largest public estates in Milan, known as San Siro. It aims at experimenting a pedagogical environment based on grounded, interactive, action-oriented and hybrid learning, reflecting how new approaches can enrich the experience of educational practices for the inclusive city. The paper addresses a series of issues, which emerge from this experience, reflecting on situated learning, the co-production of knowledge with community partners, and an action-oriented teaching practice. In this paper, a reflection on the pedagogical and social outcomes of the experience is also proposed.